Development of Electrically Controlled Liquid Crystal Phased Array Antenna - Wei XIU; Guang YANG; Haiyan TIAN; Chen PANG; Yongzhen LI; Xuesong WANG (天地一体化信息网络)
The technical background of EM metamaterials was introduced, the development history and working mechanism of electrically controlled LC technology, the latest developments in the research and application of electrically controlled LC phased array antenna were illustrated.The electrically controlled LC phased array antenna’s advantages and disadvantages were summarized.Finally, the future prospect of LC metamaterials in the fi eld of EM metamaterials was expounded.